Solar cell based on PEO, inorganic cations and ionic liquids. Issue 4 (1st July 2012) - Arunchaiya, Marisa; Jamikorn, Surassawatee; Dittrich, Thomas; Friedrich, Dennis
Abstract : Quasi-solid-state dye-sensitized solar cells (DSSCs) based on polyethylene oxide (PEO), I2 and inorganic iodides (LiI, KI, NaI, NH4 I) and/or ionic liquids ([DMIm]I, [EMIm]I, [MPIm]I, [HMIm]I) were prepared and investigated at AM1·5/10 and AM1·5 illumination conditions. Results revealed highest energy-conversion efficiencies for the PEO + I2 + LiI + [EMIm]I (60 wt%) quasi-solid-state electrolyte of 5·9% and 3·6% at AM1·5/10 and AM1·5, respectively. Moreover, it was shown (within fluctuations of the solar cells' performance) that the short circuit current density (ISC ) decreased with increasing open circuit voltage (VOC ) for electrolytes with inorganic cations; however, in the case of the solar cells prepared with ionic liquids, the ISC increased with increasing VOC . Limiting factors and reasons for fluctuations in the performance of quasi-solid-state DSSCs are discussed.